CONCEPT MAPS IN ORGANIC CHEMISTRY TEACHING - Sharma, Kanak (SCHOOL SCIENCE, 2011)
The importance of chemistry is now recognised by all educationists. Owing to its complex nature, chemistry is often full of abstract concepts. It may lead to extensive misconceptions among students. Researchers indicate (Pendley et al., 1994) that, instead of understanding the science concepts, students learn science concepts by rote learning. In our country various methods are being used to teach organic chemistry but the current methods of teaching organic chemistry are often didactic and do not involve pupil’s prior knowledge actively. Therefore, there is a need to introduce a new method of teaching organic chemistry which gives easy explanations of principles so that students become interested in chemistry and do not develop chemophobia when later faced with systemised and scientific explanation of phenomena. Use of concept maps as a teaching method is one of them. This article describes what are concept maps, why use concept maps, how to construct concept maps. It mainly describes how to construct and use concept maps. Example of phenol has been chosen to describe construction and use of concept map in teaching organic chemistry. It also emphasises on the advantages of using concept maps in teachinglearning process of organic chemistry as they can make learning an active process, can reinforce students’ understanding and learning, can improve students’ achievement in organic chemistry, can clarify misconceptions, and can be used as a tool to assess student’s understanding, etc., which can be helpful for meaningful learning in organic chemistry